Cyber-investing : cracking Wall Street with your personal computer - Brown, David L., 1940- (Wiley, 1997)
Coauthored by David Brown, founder and CEO of Telescan, the number one on-line financial information service, Cyber-Investing shows you how to unlock the potential of your PC and discover extraordinary investment opportunities. With just a click of a button you can locate: complete price and volume information on virtually any stock, analysts' long-and short-term earnings estimates, corporate financial statements, the latest insider trading news, and much more. Your new Cyber-Investing Kit offers free on-line time, as well as on-line newsletters.